XENIA NEGATIVELY AFFECTING KOPYOR NUT YIELD IN KALIANDA TALL KOPYOR AND PATI DWARF KOPYOR COCONUTS - Maskromo, Ismail; Larekeng, Siti Halimah; Novarianto, Hengky; Sudarsono, Sudarsono (Emirates Journal of Food and Agriculture, 2017)
Xenia is a phenomenon usually associated with phenotype characters controlled by a single recessive gene. The genotype of pollen donor directly determines the phenotype of fruits or seeds harvested from female recipients. Kopyor coconut is a unique coconut mutant and its formation is an example of xenia, since the genotype of the pollen donor determines the phenotype of the harvested nuts. The objectives of this research were to evaluate xenia in two types of kopyor coconuts (i.e. Kalianda Kopyor Tall and Pati Kopyor Dwarf), determine effects of homozygous KK normal and heterozygous Kk Kopyor coconut ratio, and effects of homozygous KK normal coconuts removal from mix population on yield of Kopyor nuts. For Kalianda Tall Kopyor coconut, field observations were conducted at three kopyor coconut plantations in Kalianda district, Lampung Selatan, Lampung-Indonesia while observations of Pati Dwarf Kopyor were conducted at Tayu district, Pati, Central Java-Indonesia. In both regions, coconut provenances were mapped using GPS and sub-samples were taken based on determined criteria. For each sampled tree, observations were recorded for the following variables: nut yield and yield components. The quantitative data were subjected to t-test statistical analysis to evaluate the significant differences among the observed parameters. Results of this experiment showed the presence of more homozygous KK normal coconuts among provenances of Kalianda Tall heterozygous Kk Kopyor coconut resulted in lower harvested kopyor nuts than the expected value. Moreover, removal of homozygous KK normal coconuts from a mixed coconut population increased yield of kopyor nuts. Those results indicated xenia occurred in both Kalianda Tall and Pati Dwarf Kopyor coconuts and it negatively affected the kopyor nut yield.